Amastigote Synapse: The Tricks of Trypanosoma cruzi Extracellular Amastigotes - Bonfim-Melo, Alexis; Ferreira, Eden R.; Florentino, Pilar T. V.; Mortara, Renato A. (Frontiers in Microbiology, 2018)
To complete its life cycle within the mammalian host, Trypanosoma cruzi, the agent of Chagas’ disease, must enter cells. Trypomastigotes originating from the insect vector (metacyclic) or from infected cells (bloodstream/tissue culture-derived) are the classical infective forms of the parasite and enter mammalian cells in an actin-independent manner. By contrast, amastigotes originating from the premature rupture of infected cells or transformed from swimming trypomastigotes (designated extracellular amastigotes, EAs) require functional intact microfilaments to invade non-phagocytic host cells. Earlier work disclosed the key features of EA-HeLa cell interplay: actin-rich protrusions called ‘cups’ are formed at EA invasion sites on the host cell membrane that are also enriched in actin-binding proteins, integrins and extracellular matrix elements. In the past decades we described the participation of membrane components and secreted factors from EAs as well as the actin-regulating proteins of host cells involved in what we propose to be a phagocytic-like mechanism of parasite uptake. Thus regarding this new perspective herein we present previously described EA-induced ‘cups’ as parasitic synapse since they can play a role beyond its architecture function. In this review, we focus on recent findings that shed light on the intricate interaction between extracellular amastigotes and non-phagocytic HeLa cell.